Rice-duck co-culture integrated different fertilizers reduce P losses and Pb accumulation in subtropical China. (April 2020) - Gao, Hui; Dai, Wei; Fang, Kaikai; Yi, Xiaomei; Chen, Nan; Penttinen, Petri; Sha, Zhimin; Cao, Linkui
Abstract: Double pollution with phosphorus (P) losses and potential lead (Pb) accumulation in rice fields could lead to eutrophication and crop toxicity, respectively, and affect people's health. To promote the sustainable and environmentally friendly development of agriculture, we conducted field experiments using a randomized block design to explore P losses, Pb accumulation and any potential association between P and Pb forms in rice–duck (RD) co-culture system and rice monoculture (RM) system combined with different fertilizers applied: the no fertilizer (RD and RM), chemical fertilizer (RDF and RMF), organic fertilizer (RDO and RMO), and a mixture of 70% chemical and 30% organic fertilizers (RDFO and RMFO) treatments with consistent P inputs. The results showed that RDFO had the best advantages in reducing the losses of TP (total phosphorous) (by 6.67%) and DRP (dissolved reactive phosphate) (32.72%) as well as the contents of available Pb (by 7.57%) and the accumulation of Pb in grains (26.32%) compared with RMF. RDFO also achieved the highest grain yield, reaching 10.97 t ha −1, and exhibited a lower soil weak-acid-extracted Pb (readily be taken up by plants) concentration than RDF and RMF. RDO resulted in greater TP leaching (increase by 10.62%) and lower DRP leaching (decrease by 36.57%) than RMF. It also exhibited the lowest concentration of weak-acid-extracted Pb and higher the concentration of grain Pb than that in other treatments. RDF reduced TP (by 5.33%) and DRP (by 16.36%) losses to a greater extent and the concentration of available and grain Pb were respectively 6.58% and 25.57% lower than RMF. Therefore, RDFO was the most recommended agricultural system for the studied region. Furthermore, different soil Pb forms were correlated with different P forms of soil and leakage and runoff water, which depended mainly on the fertilizer type and specific soil redox environment in the rice fields. The ratio of organic to inorganic fertilizer, the choice of organic fertilizer type, the assessment and timing of the detection of potential farmland pollution risks and association between different forms of P and Pb are worthy of further discussion. Graphical abstract: Image 1 Highlights: Rice-duck co-culture can control P leakage and runoff losses without yield loss. Rice-duck co-culture changes the pH of leakage and runoff water and thus reduce P losses. Rice-duck co-culture had potential advantage to control potential Pb transfer and accumulation. Rice-duck co-culture combined with mixed fertilization is the highly recommended.